2017
DOI: 10.31235/osf.io/a3tq9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of information – clustering books and readers in open access libraries

Abstract: Open access libraries operate in a continuum between two distinct organisation models: online retailers versus ‘traditional’ libraries. Online retailers such as Amazon.com are successful in recom-mending additional items that match the specific needs of their customers. The success rate of the recommendation depends on knowledge of the individual customer: more knowledge about persons leads to better suggestions. Thus, to optimally profit from the retailers’ offerings, the client must be prepared to share pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…8 Furthermore, clusters of German, Dutch and Italian language books tend to be more downloaded by residents from the 'corresponding' countries. 9 A recent article investigating the effects of open access at the Springer Nature e-books platform also analysed regional effects. The authors concluded that when the publication's title contained either 'Africa' or 'Latin America', this slightly increased the readership from those regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…8 Furthermore, clusters of German, Dutch and Italian language books tend to be more downloaded by residents from the 'corresponding' countries. 9 A recent article investigating the effects of open access at the Springer Nature e-books platform also analysed regional effects. The authors concluded that when the publication's title contained either 'Africa' or 'Latin America', this slightly increased the readership from those regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several other experiments have been conducted on the OAPEN Library collection: creating groups of books based on usage data (Snijder, 2019) or categorising titles based on Wikipedia pages (Snijder, 2021). In the first experiment, the download patterns are analysed to find which books are regularly selected together.…”
Section: Other Experimentsmentioning
confidence: 99%